2018
DOI: 10.1038/s41594-018-0141-6
|View full text |Cite
|
Sign up to set email alerts
|

De novo design of a non-local β-sheet protein with high stability and accuracy

Abstract: β-sheet proteins carry out critical functions in biology, and hence are attractive scaffolds for computational protein design. Despite this potential, de novo design of all β-sheet proteins from first principles lags far behind the design of all-α or mixed αβ domains due to their non-local nature and tendency of exposed β-strand edges to aggregate. Through study of loops connecting unpaired β-strands (β-arches), we have identified a series of structural relationships between loop geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
117
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(127 citation statements)
references
References 55 publications
4
117
0
Order By: Relevance
“…Computational design has been successful in mimicking the ability of evolution to generate diverse protein structures spanning helical [6][7][8][9][10] , alpha-beta [11][12][13] and beta-sheet 14,15 fold topologies, including novel folds 16 . However, most design methods do not include explicit mechanisms to vary geometric features within a topology.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational design has been successful in mimicking the ability of evolution to generate diverse protein structures spanning helical [6][7][8][9][10] , alpha-beta [11][12][13] and beta-sheet 14,15 fold topologies, including novel folds 16 . However, most design methods do not include explicit mechanisms to vary geometric features within a topology.…”
Section: Main Textmentioning
confidence: 99%
“…Previous key achievements in de novo design [11][12][13][14][15]20 focused on designing one or a few structures for diverse non-helical-bundle topologies by deriving design rules for specific topologies to identify the most favorable geometries. Proteins designed by this topology-centric strategy have pre-defined secondary structure sizes and loop torsions that are ideal to their topologies.…”
Section: Main Textmentioning
confidence: 99%
“…Marcos, E., et al identified the rules for β-arches, in which loops connect two β-strands belonging to different β-sheets, and succeeded in designing a non-local β-sheet protein, jellyroll structure, de novo (Fig. 4) [36]. Likewise, Doyle, L., et al and Brunette, T. J., et al designed α-helical tandem repeat proteins successfully de novo (Fig.…”
Section: The Rules For Designing Ideal Proteinsmentioning
confidence: 99%
“…De novo protein design is said to have come of age [1]. From the early de novo proteins confirmed by high-resolution structures [2][3][4], the field has advanced rapidly with new scaffolds covering all-a [5,6 ,7], all-b [8], and mixed-a/b and a + b structural space [9,10 ,11]. In addition, side-chain constellations can be controlled exquisitely to introduce networks of hydrogen bonds throughout target structures [12], which, in turn, can improve the design and characterisation of de novo membrane proteins [13].…”
Section: Introductionmentioning
confidence: 99%